Herman de Vries, basic values - Vries, Herman de 1931-; Arkesteijn, Roel 1974- (Fieldwork Museum, 2018)
The publication basic values documents herman de vries' exhibition of the same name in Jakarta, Indonesia. Dutch artist herman de vries, one of the most outstanding artists of his generation, has been an avowed advocate for cultural and biological diversity for decades – long before such terms started to be common. In many respects the exhibition and publication represented the fulfillment of de vries’ long-cherished desire to travel and work in Indonesia. The artist had been interested in Indonesian culture and nature for many decades, but was never in a position to visit the island nation. For the exhibition the artist realized new site-specific sculptures and installations. Appropriating local artifacts and natural materials, such as rice sickles, stems of bamboo from Bogor’s botanical garden, and baskets with rice in all its variety, the artist celebrates the cultural and biological diversity of Indonesia and the ‘basic values’ that they offer
Seite 160: "herman de vries: basic values" was commissioned by the Erasmus Huis in Jakarta as a collateral event of the Jakarta Biennale 2015 and was curated by Roel Arkesteijn. - Genaue Ausstellungsdaten ermittelt: "herman de vries - basic values", 9 November 2015 - 17 January 2016, Erasmus Huis, Jakarta
Edition: 500 copies
Keywords: Vries, Herman de -- 1931-; Geschichte 2015; Indonesien -- Motiv; Installation -- Kunst; Ausstellungskatalog -- Erasmus Huis -- 09.11.2015-17.01.2016 -- Jakarta; Bildband